Anammox attachment and biofilm development on surface-modified carriers with planktonic- and biofilm-based inoculation. (December 2020) - Tian, Xin; Schopf, Alex; Amaral-Stewart, Bianca; Christensson, Magnus; Morgan-Sagastume, Fernando; Vincent, Simon; Delatolla, Robert
Highlights: 30% less time required to achieve full biofilm coverage with detached biofilm. 3.5× higher NH4 + -N SARR for pre-seeded denitrifying carriers and detached biofilm. 13.8% preferential increase in AMX bacterial specific attachment-growth rate. Detached biofilm with pre-seeded denitrifying carriers reduces start-up of AMX MBBR. Abstract: This study investigates the kinetics, attachment, biofilm development and anammox bacteria enrichment of a novel detached anammox biofilm inoculation method on non-modified virgin MBBR carriers and pre-seeded denitrifying carriers. The study compares these results to the more common use of attached anammox carriers for anammox MBBR inoculation. The anammox bacteria specific attachment-growth rates for virgin carriers inoculated with detached anammox biofilm mass were 38.1% greater for the first 25 days, leading to approximately 30% less time required to achieve complete biofilm coverage than those measured in attached biofilm carrier inoculated systems during the attachment and early biofilm growth stages. The biofilm thickness increase rate was also 52.3% higher for virgin carriers with detached biofilm inoculum. Further, inoculation using pre-seeded denitrifying carriers compared to virgin carriers demonstrated a 13.8% preferential increase in anammox bacteria specific attachment-growth rate and a corresponding 47.2% higher NH4 + -N removal rate at the time of biofilm maturation.